Study of the Thermal Stability of Ginsengbiomass as a Drying Object - S. Koshkalov, Evgeny; P. Talipova, Irina; P. Talipova, Lida; Feoktistova, A.; P.Barylnicova, Elena (International Journal of Engineering and Technology, 2018)
The problem of receiving biologically active medicines of a broad spectrum of activity for the food, pharmaceutical, cosmetic industry is relevant results of a research of heat stability of biomass of a ginseng for the purpose of justification of temperature condition and a way of drying are presented. Influence of duration and temperature of heating on quality indicators of biomass of a ginseng is studied. It is experimentally established that at a temperature of 400C and durations of heating within 15 hours the maintenance of total glycoside fraction in biomass of a ginseng (SGF) decreases up to 50%; at a temperature of 1000C and durations of heating within 8 hours of SGF about 30% decrease. It is revealed that at a temperature of heating up to 40 0C with increase in duration of heating increase in speed of process of a thermal inactivation is observed. It is established that the admissible temperature of heating of biomass of a ginseng is 600C. At sublimation drying the maintenance of SGF in dry biomass of a ginseng is 1,5 - 2 times higher, than at convective and vacuum drying. On the basis of results of a research the conclusion is drawn on that sublimation drying is the most preferable way of drying in comparison with vacuum and convective, allowing to receive a dry product with the highest quality indicators.Â Â